IDEAL RECONSTRUCTION OF REHABILITATION PUNISHMENT FOR NARCOTICS ADDICTS AND ABUSER'S VICTIMS JUSTIFIED BASED ON THE LAW OF THE REPUBLIC OF INDONESIA NO. 35 YEAR 2009(CASE STUDY IN SUMATERA UTARA PROVINCE) - Ahmad Zaini; Gunarto Gunarto; Darwinsyah Minin (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
The Law of The Republic of Indonesia No. 35 year 2009 article 54 states that every drug addicts and abusers’ victims shall undergo medical rehabilitation and social rehabilitation, affirmed on article 103 that explains the Judge who examines the case of narcotics addicts, may decide to order the concerned to undergo treatment and/or treatment through rehabilitation, if the narcotics addict are proven guilty of a crime of narcotics, or set out to order the concerned to undergo treatment and/or treatment through rehabilitation, if the Narcotics Addict is not found guilty of a crime of Narcotics. For the Law of The Republic of Indonesia No. 35 year 2009 above to be done, a Joint Regulation between 7 (seven) Ministries/Institutions about The Handling of Narcotics Addicts and Abuser’s Victims into Rehabilitation Institutions was made in order to create an equation of perception about the punishment that should be dropped for narcotics addicts and abuser’s victims defendants is for them to be punished or set in to rehabilitation. However, in Sumatera Utara Province the narcotics addicts and abusers victims defendants are obviously set to be imprisoned for 2 – 4 years long, or even more. In other words, the rehabilitation penalty is still so far from expectation compared to imprisonment. The purpose of this script is to acknowledge the obstacles and interferences that cause the Judge to set the narcotics addicts and abuser’s victims defendants into imprisonment more than to order and/or set them out to undergo rehabilitation treatment. It is also to look further to the investigation process by the investigator, continued by the prosecution by the Prosecutor, up until the Judge’s judgement and its implementation in correctional facilities or rehabilitation institutions. Furthermore, the ideal reconstruction that should be done in order to the Law of The Republic of Indonesia No. 35 year 2009 about the narcotics addicts and abuser’s victims to be effectively functionate, where the punishment of the narcotics addicts and abuser’s victims is to be judged or set out to undergo treatment through rehabilitation. The theories used in this research are 1) Grand theory, which is The Theory of Justice, 2) Middle theory, which consists of Theory of Protection and Theory of the Work of Law, 3) Applied Theory, which includes The Theory of The Purpose of Law and The Theory of Progressive Law. The Law of The Republic of Indonesia No. 35 year 2009 is based on justice, therefore it needs some reconstruction on the article 127 so that it would not create any doubt in the action because it is considered to develop ambiguous interpretation due to its indecisiveness that leads it to be the last article of the law in judging the narcotics addicts and abuser’s victims defendants position. The reconstruction of The Law of The Republic of Indonesia No. 35 year 2009 article 127 is expected to deprive the interpretation dualism of the narcotics addicts and abuser’s victims defendants.Keywords : Rekonstruction, Rehabilitation Punishment, Narcotics Addicts and Abuser’s Victims.